Biomass-derived polyphosphazene toward simultaneously enhancing the flame retardancy and mechanical properties of epoxy resins. (January 2023) - Xiao, Yuling; Mu, Xiaowei; Chen, Siqi; Jiang, Guangyong; Xu, Zhoumei; Ma, Chao; Song, Lei; Hu, Yuan
Abstract: As one of the most widely used polymers, the intrinsic brittleness and high flammability bring about a stringent requirement for the practical application of epoxy resins (EPs). It is difficult to toughen EP without compromising its mechanical and thermal properties for many conventional toughening agents. Here, a novel furan-derived bio-based polyphosphazene (PFMP) with a flexible backbone and rigid side groups was prepared by the nucleophilic substitution reaction between polydichlorophosphazene (PDCP) and furfuralcohol. The resultant PFMP was incorporated into EP to realize exceptional toughening, strengthening, and flame retardant function. By adding 15% of PFMP, the limit oxygen index value is from 25% (EP) to 33% (EP/PFMP-15) and reaches the UL-94 V-0 rating. According to the cone calorimeter results, EP/PFMP-15 exhibits exceedingly reduced peak heat release rate (pHRR) (50.2%) and total heat release (THR) (49.6%). The significantly increased fire performance index (FPI) and decreased fire growth rate index (FIGRA) of EP/PFMP-15 demonstrate an improvement in its flame retardancy. The catalytic carbonization effect (condensed phase) and radical quenching effect (gas phase) of PFMP account for the greatly improved flame retardancy. Moreover, the impact and tensile tests indicate that PFMP can ameliorate the mechanical performance of EP with a maximum increase of impact strength (111.8%) and elongation at break (35.2%) for EP/PFMP-5. With 15% PFMP added, the tensile strength of EP/PFMP-15 increases by 40.4%. This work demonstrates that PFMP is expected to overcome shortcomings (ﬂammability, toughness, and strength) of EP and spread its applied fields. Graphical abstract: Image 1 Highlights: Bio-based polyphosphazene with furfuralcohol side groups (PFMP) was synthesized. PFMP exhibits evident flame retardant and mechanical enhancement effect on epoxy resins (EP). The peak heat release rate of EP/PFMP-15 was 50.2% lower than pure EP. The impact strength of EP/PFMP-5 was 111.8% higher than pure EP.